Influence of interface intermixing and periodicity on internal electric field and polarization in ferroelectric superlattices - Chew, Khian Hooi; Iwata, M.; Lim, K.G.; Ong, L.H. (2013)
A thermodynamic model is developed to study the effect of interface intermixing and modulation period on the internal electric field of a superlattice comprising alternate layers of ferroelectric and dielectric. The intermixed layer plays an important role in determining both the polarization and internal electric field modulation profiles of the superlattice. The presence of interface intermixed layer gives rise to inhomogeneous internal field and polarization, which enhances the depolarization field of the superlattices. Interface intermixing; however, does not have much influence on the polarization behavior of the superlattice. Ferroelectric volume fraction or thickness ratio of ferroelectric to dielectric is one of the key parameter for controlling the properties of a superlattice consisting alternate layers of ferroelectric and dielectric. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.